(untitled) (Research, Society and Development, 2022)
The cultivation of second crop corn has been consolidating in the states of the Center-South of Brazil and has been increasingly adopted by producers. And in order to obtain high yields, it is important to carry out the nutritional management of the plants. The aim of the present study was to evaluate the agronomic performance of corn hybrids submitted to the application of doses of magnesium via foliar. The experiment was carried out at Fazenda Córrego do Oriente in Nova Glória - GO in an area under no-tillage. The experimental design was randomized blocks in a 5x2 factorial scheme, five doses of magnesium (0; 0.25; 0.50; 0.75 and 1.0 kg ha-1) and two corn hybrids (P 4285VYHR and MG 580PWU) with four replications. The variables analyzed were: plant height, height of the first ear, ear diameter, ear length, number of rows of grains, number of grains per row, weight of one thousand grains, productivity. There was no significant difference in doses in any of the variables. For the variables AP, CE, M1000 and PROD the hybrid P 4285VYHR was superior, presenting higher means. The dose of 0.370 kg ha-1 contributes to greater productivity gains.